Technological quality of special bean grains during storage - Cavalcante, Adailza Guilherme [UNESP]; Meirelles, Flávia Constantino [UNESP]; Filla, Vinicius Augusto [UNESP]; Cavalcante, Alian Cássio; Lemos, Leandro Borges [UNESP] (Nativa, 2024)
The objective was to evaluate the effect of storage of special bean grains at room temperature on the qualitative characteristics. Nine bean cultivars with special grains were used: BRS Radiante, BRSMG Realce, BRS Pitanga, BRSMG Treasury, BRS Marfim, BRSMG União, IAC Tigre, EPAMIG Ouro Vermelho and EPAMIG Ouro da mata, during five storage periods: freshly harvested, 60, 120, 180 and 240 days after storage, except the crude protein content of the grains, which were evaluated in three periods (newly harvested, 120 and 240 days). The grains were packed in closed plastic packages (15.5 x 12 cm), with 1.5 kg of grain, using four replications per cultivar and stored in ambient conditions. The following were evaluated: grain moisture, crude protein content, cooking time, maximum hydration time, hydration ratio, soaking before cooking, volumetric expansion and whole grains after cooking. The storage period influenced the parameters evaluated in all cultivars used. There is a reduction in the technological characteristics of the grains with the storage period, except for the moisture content, cooking time and hydration ratio. Grains stored after 120 days increase the cooking time and hydration ratio.
Qualidade tecnológica de grãos de feijoeiro especial durante o armazenamento
Keywords: food safety; Phaseolus vulgaris L.; room temperature